Educational intervention in the improvement of healthy lifestyles and health self-care of women in the glass of milk program - Prado Juscamaita, Justina Isabel (2025)
Objective. Demonstrate the effectiveness of educational intervention in improving healthy lifestyles and self-care for adult women in the glass of milk program of the Municipality of Pillcomarca, Huánuco, Peru. Methods. We worked with a quasi-experimental design of pre and post test of a single group, whose sample was 26 women leaders. Before and after the intervention, the evaluation tests were applied to measure healthy lifestyles and self-care. Results. Regarding the results found before the educational intervention, 57.7% had unhealthy lifestyles, decreasing in the post-test to 7.7%; while in relation to healthy lifestyles, 46.2% in the pre-test increased to 92.3% in the post-test. Likewise, in terms of inadequate self-care practices, 92.3% in the pre-test decreased to 53.8% after the intervention. Conclusion. Adequate self-care practices in the pretest from 7.7% increased to 46.2% in the posttest; and healthy lifestyles of 46.2% in the pre-test increased to 92.3%, clearly showing the positive effect of the educational intervention towards a behavior favorable to women's health.